Hamilton Ranch - Richard L. Allman:::Creator::::::::::::
Twenty-five images and views of the old Hamilton Ranch, which belonged to Steinbeck's mother's parents. Photo numbers. 0-686, 0-687, 1-766 included on this sheet. RESTRICTED USE